PENGARUH PERUBAHAN NILAI TUKAR RUPIAH TERHADAP RETURA' SAHAM MELALUI PERUBAHAN ARUS KAS DAN PERUBAHAN EARNING PER SHARE (EPS): BUKTI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - LIA INDRIYATI KURNIAWAN (Jurnal Riset Akuntansi dan Keuangan, 2006)
The srudy is ot empirical one wlnse pwposes or,e to prove if exclwnge rate'risk have a positive inJluence in stock return from earning per share alteration and cash flow alteration. Samples which are used in this stu$t are 192 data of manufacturing corporations that listed inBEI. The period of sudy is 199&2004. &atistic mdels which are used in this study are simple regression od multiple regression analysis. Tlwre,wefow models used in this study. TTtere ue, model I and model II are used to prove if information of eorning per share alteration and cash flow alteration ltove a positive intluence for cumulative abnormal return. Model III and Model IY are used to pnove if exchange rate risk have a positive infiuence for earning per share alteration and cash flow alteration.The results are information of earning per share alteraion and cash flow alteration have not a positive inJluence for cumulative abnormal return, exchange rate risk have not a positive influence in eorning per share, but exchange rate risk altergtion have a positive influence for cash flow alteration.Keywords: Real Exchange Rate, Earning Per Share, Cash Flow